Encapsulation of the lipidated TLR7/8 agonist INI-4001 into ionic liposomes impacts H7 influenza antigen-specific immune responses - Fatemeh Mehradnia; Hardik Amin; Maria E. Ferrini; Haley Partlow; Timothy Borgogna; Soma Shekar Dachavaram; Kendal T. Ryter; Hélène G. Bazin; Jay T. Evans; David J. Burkhart; Blair DeBuysscher; Walid M. Abdelwahab (Drug Delivery and Translational Research, 2026)
Toll-like receptors (TLRs) are the best characterized family of Pattern Recognition Receptor-targeting adjuvants. Activation of TLR7/8 in particular, enhances antigen presentation by dendritic cells and macrophages, boosting Th1-mediated adaptive immune responses. However, poor pharmacokinetics and systemic toxicity of some TLR7/8 ligands hinder their clinical translation. Lipidation and incorporation of TLR7/8 ligands into liposomes can reduce systemic exposure, improve pharmacokinetics, pharmacodynamics, and presentation to immune cells. In the present study, a series of liposomal formulations incorporating a novel lipidated TLR7/8 agonist, INI-4001, were prepared to evaluate the effect of surface charge and lipid composition on the colloidal stability, cytotoxicity, innate immune activation, and adjuvant activity when combined with the recombinant Influenza A/Shanghai/1/13 (H7N9) Virus Hemagglutinin antigen (H7). The tested formulations include neutral (DOPC/Cholesterol), anionic (DOPG/Cholesterol), and cationic (DOPC/DC-Cholesterol, DOPC/GL67, DOEPC/Cholesterol, DOTAP/Cholesterol, or DOTAP + DDAB/Cholesterol) liposomes. These studies demonstrated that alongside the type and magnitude of particle surface charge, lipid composition was a determining factor in the regulation of immunogenicity and biocompatibility of INI-4001-loaded liposomes. Among the cationic liposomes evaluated, DOPC/DC-Cholesterol liposomes exhibited the lowest in vitro cytotoxicity while enhancing TNF-α induction from human peripheral blood mononuclear cells. Furthermore, murine immunization studies demonstrated that the same formulation enhanced H7-specific IgG titers and induced a Th1-polarized cell-mediated response compared to H7 antigen alone or the matched liposome lacking INI-4001. Of note, the anionic DOPG/Cholesterol INI-4001 liposomes induced a rapid response with significantly higher IgG titers after a single immunization and promoted strong Th1-polarized cellular responses, which may be advantageous in an influenza pandemic setting. These findings highlight the key role of liposome characteristics in optimizing the safety and immunogenicity of TLR7/8 agonist-adjuvanted subunit influenza vaccines.